Effect of elevation and canopy condition on morphological traits and leaf fluctuating asymmetry of a bamboo, Chimonobambusa utilis in Jinfo Mountain Nature Reserve, Southwest China - Qing, Yu Li; Zhuo-Wen Zhang, Wen Zhang; Jian, Ping Tao; Jiang, Hua Liu; Xiao, Hui Yong; Xue, Feng Meng; Zhen, Li; Yong, Jian Wang (Universiti Kebangsaan Malaysia, 2014)
Due to widespread distribution of dwarf bamboo, Chimonobambusa utilis, in mountain environment, the effects of elevation (low and high) and canopy condition (forest understorey and forest edge) on the clonal morphology and leaf fluctuating asymmetry were investigated in an evergreen broadleaves forest of Jinfo Mountain Nature Reserve. Elevation and canopy condition were significant for all morphological traits of C. utilis (except for effect of elevation on node number under branch). Traits of clonal morphology such as height, basal diameter, height under branch tended to be higher in forest understorey and in high elevation. Forest understorey in high elevation was favour of shooting number. Interaction of elevation and canopy conditions had a significant effect on growth of node. Single leaf area (SLA) and all indices of fluctuating asymmetry were significantly higher in low elevation than that in high elevation of forest understorey. Thus, elevation and canopy condition formed environmental stress that lead to the adaptation of morphological traits and leaf fluctuating asymmetry of C. utilis populations to mountain forest habitats.